THE EFFECT OF SCOUTING EXTRACURRICULAR ON STUDENTS’ DISCIPLINE AT SD NEGERI 4 ABUAN SUSUT DISTRICT, BANGLI REGENCY - I Nyoman Sudirman; I Wayan Numertayasa; I Wayan Rendana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research focused on the effect of scouting extracurricular on the students’ discipline at SDN 4 Abuan. The subjects in this study were 25 students of SD Negeri 4 Abuan. Data were obtained through a questionnaire. Then, the data were analyzed by the correlation analysis of causal relationships with SPSS (Statistical Package for Social Science) version 25.0 and the results of the analysis were quantitative scores. The results obtained that scouting extracurricular significantly influenced the students’ discipline at SD Negeri 4 Abuan, Kecamatan Susut, Kabupaten Bangli. This conclusion was supported by the average score obtained from the students which were 80.13 and 81.30 (Excellent). In addition, it was found that the influence of scouting extracurricular on students’ discipline had a positive and significant effect. This was indicated by the correlation coefficient of 0.925 or 92.5%, meaning that the score was at an interval of 0.80–1.00. Thus, there was a very strong influence between variable X (Extracurricular Scout) and variable Y (Student Discipline), and the results of the test (sig. 2-tailed (0.05)) resulted in a figure of 0.000 so that this number was less than the significance value of 0.05 (0.000 < 0.05). This indicated that there was a positive and significant effect between the two variables. Based on the results of the correlation coefficient (R), simple linear regression analysis, and the significance test (T test), it was concluded that the extracurricular positively and significantly influenced the students’ discipline at SD Negeri 4 Abuan, Kecamatan Susut, Kabupaten Bangli.